CERITA LAMA FREPORT DALAM PEMBANGUNAN EKONOMI - Suharyono - (Universitas Nasional, 2017)
The purpose of this study is giving a comprehensive and critical explanation about necessary action or effort which should be carried out to overcome the Freeport’s dilemma connected with Science Philosophy, Business Ethics, Corporate Social Responsibility (CSR), and Good Corporate Governance (GCG). The data discussed in this study is a secondary data obtained mainly from web sites and on line media (2005 and 2007). The discussion result showed that most of the comments by Freeport’s managements in their report didn’t support the real condition. Business Ethics Implementation, CSR and GCG at the company were basically uncertain and doubtful in supporting the sustainable development. Freeport has been a dilemma which is necessary to be handled wisely by respecting proportionally the stakeholders’ necessity of the company both primary and secondary. It is necessary for that reason to create ownership proportionality, to determine the rule and regulation and to conduct the law enforcement in accordance with law resemblance.